SEJARAH BADAN PEMULASARAN JENAZAH TIONGHOA MALANG PADA MASA KOLONIAL (1905-1940) - Labibah, Annisaa Khansa (Universitas Negeri Malang, 2022)
This research will discuss the Chinese funeral of the corpse agency in Malang during the Dutch East Indies colonial period. The development of Chinese ethnicity in Malang yearly has increased quite rapidly. The growth of the Chinese community in Malang has encouraged some people to form 'groups of harmony', to avoid conflict and help with death. This association was formed in 1905 named Thian Tee Hwee, then in 1910 changed its name to Ang Hien Hoo, along with the registration of this association as a legal entity in the Dutch East Indies. This association is engaged in many socio-cultural fields. The most visible social activity related to the funeral of corpses was the assistance of the funeral corpses for the underprivileged Chinese.Penelitian ini akan membahas mengenai badan pemulasaran jenazah Tionghoa di Malang pada masa colonial Hindia-Belanda. Perkembangan etnis Tionghoa di Malang dari tahun ketahun mengalami peningkatan yang cukup pesat. Pertumbuhan komunitas Tionghoa Malang mendorong beberapa orang membuat ‘perkumpulan kerukunan’, untuk menghindari konflik dan membantu urusan kematian. Perkumpulan ini dibentuk pada 1905 bernama Thian Tee Hwee, lalu pada 1910 berganti nama menjadi Ang Hien Hoo, bersamaan dengan terdaftarnya perkumpulan ini ke badan hukum di Hindia Belanda. Perkumpulan ini banyak bergerak dibidang sosial-budaya. Kegiatan sosial yang paling terlihat terkait pemulasaran jenazah, adalah bantuan pemulasaran jenazah untuk orang Tionghoa yang kurang mampu.